Human Fasciolosis: Might it be Occurred in Indonesia? - Widjajanti, S (Indonesian Animal Sciences Society, 2004)
Fasciolosis is known as a common parasitic disease in ruminants. However, in the last thirty years there were reports of high evidence on human fasciolosis in many countries, such as South America, Africa, Europe, Australia, New Zealand and South East Asia. Fasciolosis in human is caused by trematodes, such as Fasciola hepatica and F. gigantica, and there is no report of human Fasciolosis in Indonesia caused by F. gigantica, except human fasciolopsiasis caused by Fasciolopsis buski. The prevalence of fasciolosis in ruminants in Indonesia is up to 90% and people in some parts of Indonesia like to consume raw vegetables; this habit is assumed to be able to spread fasciolosis in human. Therefore, caution on the occurrence ofthe disease in human, particularly those living in the farming areas ofendemic fasciolosis that have a habit of consuming raw vegetables needs to be enhanced through epidemiological investigation by using an accurate diagnostic technique. Key words: Human fasciolosis, Indonesia, epidemiology study